Peningkatan Motivasi dan Hasil Belajar Melalui Metode Buzz Group - Hardayanti Bahning (Institut Agama Islam Negeri Palopo, 2019)
This research supported by the lack of motivation and learning outcomes islamic education students educated at. vocational schoolThe purpose of this research to know the learning methods he continued to buzz can increase motivation and learning outcomes in learning. islamic educationThis study research the act of class ( class room action research conducted ). cycle as much asThe subject is the muslim students xi route tourism state 1 integrated luwu ponrang 24. as the southData collection techniques used is, observation the survey and by using an instrument shaped double. about choiceData analyzed using analysis. descriptiveThe analysis of data observation students at cycle i obtained the average percentage of the students only 50.044 % ( low ) increased to percent of high 82.22 in cycle II. The spread of chief motivation students on cycle i obtained the average the percentage motivation students only of 59,75 % ( being ) increased to 71.5 % ( high in cycle ii) .Next based on hasi analysis student learning test study results obtained the average students on pre cycle of 62.167 ( less of the total value 1492 with the ketuntasan klasikal is only 29.17 % , you are an increase of cycle i with the average score of 67.667 ( less ) while the up 37.5